The Role of Islamic Religious Education Teachers in Educating Students on Identity Issues and Adolescent Social Relationships at SMAN 1 Kadugede - Muhammad Rakan Nazhief Rabbani; Prasetyo Wardana; Ridwan Maulana Nurfuadi; Edi Suresman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The social and psychological development of adolescents in the identity search phase often clashes with the unfiltered flow of global information that dynamically shifts values and social relationship patterns. This makes schools one of the places for character building. In this context, Islamic Education teachers have a strategic position in guiding and directing students to understand their identity and build social patterns in accordance with moral and religious values. This study aims to analyze the strategic function of PAI teachers in educating adolescents on issues of identity and social interaction at SMAN 1 Kadugede. This study uses a quantitative approach with a descriptive research type. The research sample consisted of 5 teachers islamic education and 60 12th grade students at SMAN 1 Kadugede who were determined using purposive sampling techniques. The data analysis technique used descriptive statistical analysis in the form of percentages. The results of the study indicate that Islamic Religious Education at SMAN 1 Kadugede has a positive contribution to character building and students' understanding of moral values. Therefore, strengthening the role of PAI teachers is an important aspect in efforts to build student character at school.